2000
DOI: 10.1006/prep.2000.1255
|View full text |Cite
|
Sign up to set email alerts
|

Expression of an Anti-CD3 Single-Chain Immunotoxin with a Truncated Diphtheria Toxin in a Mutant CHO Cell Line

Abstract: ADP-ribosylating immunotoxins are generally expressed in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“…Based on our understanding of the processing and secretion of ␣-factor in S. cerevisiae (37), we expect that after entering the endoplasmic reticulum (ER), the preproimmunotoxin undergoes initial processing to remove the presequence, followed by folding and N-linked glycosylation at the three potential sites in the prosequence region. Potential glycosylation sites of the immunotoxin have been removed (22). The proimmunotoxin could then be transported from the ER to the Golgi complex, where it might undergo further modification of oligosaccharide chains before it is finally processed to yield the immunotoxin by proteolytic cleavage at the Kex2 site introduced between the prosequence and the immunotoxin.…”
mentioning
confidence: 99%
“…Based on our understanding of the processing and secretion of ␣-factor in S. cerevisiae (37), we expect that after entering the endoplasmic reticulum (ER), the preproimmunotoxin undergoes initial processing to remove the presequence, followed by folding and N-linked glycosylation at the three potential sites in the prosequence region. Potential glycosylation sites of the immunotoxin have been removed (22). The proimmunotoxin could then be transported from the ER to the Golgi complex, where it might undergo further modification of oligosaccharide chains before it is finally processed to yield the immunotoxin by proteolytic cleavage at the Kex2 site introduced between the prosequence and the immunotoxin.…”
mentioning
confidence: 99%
“…Furthermore, the bivalent immunotoxin production in an EF-2 mutant CHO cell expression system was limited to 5 mg/liter and could not be increased by selection for multiple gene insertions (Neville, unpublished data). Due to this limitation, except for three reports from our laboratory (12,20,25), all recombinant immunotoxin production for therapeutic uses has been limited to Escherichia coli production, which has required denaturation and refolding from inclusion bodies (6). However, refolding of the multidomain structure of the bivalent immunotoxin from E. coli was inefficient, and complete bioactivity was not recovered (25).…”
mentioning
confidence: 99%
“…Correct post-translational modifications can support functionality of eukaryoticderived proteins. Although expression of immunotoxins has been theoretically limited because the products are toxic to the producing cells as soon as they reach the cytosol, some groups have reported the successful synthesis of immunotoxins in eukaryotic cells in vitro and in vivo (Chen et al 1997;Vallera et al 2000;Liu et al 2000;Jia et al 2008). These researchers found that the transfected eukaryotic cells retained their viability while continuously secreting immunotoxin proteins.…”
Section: Discussionmentioning
confidence: 98%